Risk aversion loss aversion, and the demand for insurance - Louis Eeckhoudt; Anna Maria Fiori; Emanuela Rosazza Gianin (Risks, 2018)
In this paper we analyze insurance demand when the utility function depends both upon final wealth and the level of losses or gains relative to a reference point. Besides some comparative statics results, we discuss the links with first-order risk aversion, with the Omega measure, and with a tendency to over-insure modest risks that has been been extensively documented in real insurance markets.
Keywords: 330; first-order risk aversion; stochastic dominance; insurance; expected utility